2022
DOI: 10.3390/ijerph19010497
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Differentiation and Influencing Factors of Water Pollution-Intensive Industries in the Yellow River Basin, China

Abstract: The structure adjustment and layout optimization of water pollution-intensive industries (WPIIs) are crucial to the health and sustainable development of the watershed life community. Based on micro-detailed data of Chinese industrial enterprises from 2003 to 2013, we analyzed and revealed the spatial differentiation characteristics and influencing factors of WPIIs in the Yellow River Basin (YRB) from 2003 to 2013 by constructing a water pollution-intensive index and integrating kernel density estimation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Many studies have found that economic development, environmental awareness, and spatial variation characteristics are the main drivers of industrial wastewater, , which directly affects water quality . More factors affect the investment in industrial wastewater pollution treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found that economic development, environmental awareness, and spatial variation characteristics are the main drivers of industrial wastewater, , which directly affects water quality . More factors affect the investment in industrial wastewater pollution treatment .…”
Section: Resultsmentioning
confidence: 99%
“…𝑑 (11) where 𝛤(𝐴) greater than 0 indicates that the spatial distribution of industry 𝐴 is agglomerated in the region; otherwise, it is considered random or dispersed. A larger 𝛤(𝐴) signifies a more significant agglomeration of industry 𝐴 in the region.…”
Section: 𝛤(𝐴) = ∑ 𝛤(𝐴 𝑑)mentioning
confidence: 99%
“…A suitable industrial agglomeration pattern, which considers both the agglomeration degree and the cluster location, can facilitate firms in benefiting from the industrial agglomeration effect and acquiring clear advantages in terms of cost, productivity, and innovation environment [5][6][7][8][9][10]. It serves as a crucial force for the high-quality and sustainable development of regions and cities [11][12][13][14][15]. A comprehensive analysis of industrial agglomeration patterns helps evaluate the performance of existing policies and formulate new ones, thereby promoting the development of a more suitable industrial agglomeration pattern [10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to strengthen water management in the middle and upper reaches of the provinces (such as QH and NMG), change their unsustainable water use, and improve industrial water efficiency. Meanwhile, the distribution of water pollution-intensive industries in downstream provinces should be reduced to improve the overall decoupling level (Du et al, 2022). Compared with the agricultural sector, the decoupling status difference between industrial water use and economic development level among provinces is mainly caused by the imbalance of economic development among provinces (Qiao et al, 2021).…”
Section: Driving Factors Of Water Use In Different Sectorsmentioning
confidence: 99%